Beneficial developmental acclimation in reproductive performance under cold but not heat stress - Simões, Pedro (2020)
Thermal plasticity can help organisms coping with climate change. In this study, we analyse how laboratory populations of the ectotherm species Drosophila subobscura, originally from two distinct latitudes and evolving for several generations in a stable thermal environment (18 °C), respond plastically to new thermal challenges. We measured adult performance (fecundity traits as a fitness proxy) of the experimental populations when exposed to five thermal regimes, three with the same temperature during development and adulthood (15-15 °C, 18-18 °C, 25-25 °C), and two where flies developed at 18 °C and were exposed, during adulthood, to either 15 °C or 25 °C. Here, we test whether (1) flies undergo stress at the two more extreme temperatures; (2) development at a given temperature enhances adult performance at such temperature (i.e. acclimation), and (3) populations with different biogeographical history show plasticity differences. Our findings show (1) an optimal performance at 18 °C only if flies were subjected to the same temperature as juveniles and adults; (2) the occurrence of developmental acclimation at lower temperatures; (3) detrimental effects of higher developmental temperature on adult performance; and (4) a minor impact of historical background on thermal response. Our study indicates that thermal plasticity during development may have a limited role in helping adults cope with warmer - though not colder - temperatures, with a potential negative impact on population persistence under climate change. It also emphasizes the importance of analysing the impact of temperature on all stages of the life cycle to better characterize the thermal limits.